Gen Y’s Needs and Intention to Stay in the Banking Sector, Mediated by Perceived Organizational Support - Zabedah Othman; Raemah Abdullah Hashim; Zulaika Zakariah, (Open University Malaysia (OUM), 2017)
Previous studies have shown that banks in Malaysia play a critical role in generating spillover effects to other sectors and creating new industries for the economy. However, in today’s competitive corporate environment, especially in the banking sector, retaining their highly skilled and knowledgeable employees is still one of their biggest challenges. Despite numerous perks, rewards and benefits given to the Gen Y employees, pastscholars have found that the employers were still not able to retain them. Gen Y are known for their technological and internet expertise, however, they are seemed to be outspoken, not loyal, and unable to stay long in an organization. Therefore, the aim of this concept paper is to determine the impact of social, emotional and learning needs towards the intention to make Gen Y employees stay in the banking sector in Malaysia. Incapable of retaining the Gen Y employees will make employers incur severe losses in terms of money, rapid recruitment, training and career succession planning. Therefore, to maintain high quality, competent and knowledgeable employees, we must understand the Gen Y’s intention to stay with regard to their social, emotional and learning needs. Consequently, we can plan and implement contemporary human resource functions related to this young generation effectively, in order for them to perform their duties diligently and how they could be retained in the banking industry. (Abstract by authors)